Design of strain-hardening natural TRM composites: current challenges and future research paths - Illampas, Rogiros (2023)
This paper discusses the challenges in using natural fibers for the development of textile-reinforced mortar (TRM) composites with pseudo-strain-hardening and multiple cracking behavior. The particular characteristics of natural vegetal fibers are analyzed with reference to data from the literature. It is concluded that the efficient use of these fibers as composite reinforcement requires the development of treatment or impregnation protocols for overcoming durability issues, eliminating crimping effects in tensile response and imparting dimensional stability. Relevant experimental research on the synthesis and performance of natural TRMs is reviewed, showing that the fabrication of such systems is, at present, largely based on empirical rather than engineering design. In order to set a framework regarding the properties that the constituents of natural TRM must meet, a comparative analysis is performed against inorganic matrix composites comprising synthetic, mineral and metallic reinforcement. This highlights the need for selecting matrix materials compatible with natural fibers in terms of stiffness and strength. Furthermore, a rational methodology for the theoretical design of natural TRM composites is proposed. First-order analysis tools based on rule-of-mixtures and fracture mechanics concepts are considered. Based on the findings of this study, paths for future research are discussed.